Agricultural sustainability and environmental change at ancient Gordion - Marston, John M. (University Museum monograph. Gordion special studies, 2017)
This book publishes the results of 220 botanical samples from the 1993-2002 Gordion excavations directed by Mary Voigt. Together with Naomi Miller's 2010 volume (Gordion Special Studies 5), this book completes the publication of botanical samples from Voigt's excavations. The book aims to reconstruct agricultural decision making using archaeological and paleoenvironmental data from Gordion to describe environmental and agricultural changes at the site. John M. Marston argues that different political and economic systems implemented over time at Gordion resulted in patterns of agricultural decision making that were well adapted to the social setting of farmers in each period, but that these practices had divergent environmental impacts, with some regimes sponsoring sustainable agricultural practices and others leading to significant environmental change. The implications of this book are twofold: Gordion will now be one of the best published agricultural datasets from the entire Near East and, thus, serve as a valuable comparable dataset for regional synthesis of agricultural and environmental change, and the methods the author developed to reconstruct agricultural change at Gordion serves as tools to engage questions about the relationship between social and environmental change at sites worldwide. Other books address similar themes but none in the Near East address these themes in diachronic perspective such as we have at Gordion. Museum Monograph 145.